Zebrafish larva interface: an accessible, modular platform for Danio rerio experiments - Jutoy, John; Mehrabi, Hossein; Jung, Erica E. (Frontiers in Neuroscience, 2025)
The optokinetic response (OKR) in larval zebrafish (Danio rerio) is a well-characterized visuomotor reflex used to investigate sensorimotor integration. Building on prior work, we introduce the zebrafish larvae interface (ZLI) platform, a modular and accessible framework that enables closed-loop neuro-robotic experiments. We investigated how larval OKR behavior can translate to dynamic motion control of a wheeled robot. The platform incorporates an agarose stamping methodology to head-fix a larva while preserving full ocular mobility and visual access. Eye movements are recorded in real time using either a low-cost webcam or a microscope camera and processed through open-source computer vision software, which extracts eye angles via ellipse fitting. These measurements are translated into movement commands for a robot navigating a line-following task. The robot’s positional deviation is simultaneously converted into dynamic OKR-compatible visual stimuli displayed on an LCD screen beneath the larva, thus completing the sensorimotor loop. We demonstrate that the ZLI system enables larvae to robustly correct robot trajectories after substantial initial misalignment. By emphasizing modularity, affordability, and replicability, the ZLI system aims to democratize access to closed-loop behavioral research and promote widespread adoption in both educational and experimental neuroscience environments.